And the killing goes on ; Patented drugs ; Anno XV Inno Sotto [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Focuses on Amnesty International and the continuing struggle of Filipino to stop violence. Debate rages on whether to junk the patent law or not. Fashion designer Inno Sotto presents his latest collection.
And the killing goes on (18 min.) -- Patented drugs (14 min.) -- Anno XV: Inno Sotto (15 min.)
VHS
Keywords: Soto, Inno -- Interviews; Civil rights -- Philippines; Costume design -- Philippines; Drugs -- Patents. -- Philippines; Fashion designers -- Philippines; Patent laws and legislations -- Philippines; Political atrocities -- Philippines